Renal denervation for hypertension: cross-country cost-effectiveness insights from mainland China, Japan, and Thailand - Dai Lian; Yue Suo; Ruoyan Gai; Ning li; Yunfeng Ren; Dunming Xiao; Jiaxin Zhao; Mingdong Zhang; Shimeng Liu; Yingyao Chen (Health Economics Review)
Abstract Background Renal denervation (RDN) has been introduced as a novel non-pharmacological intervention for patients with hypertension that is poorly controlled by pharmacological means. Our study aims to evaluate the cost-effectiveness of the Netrod RDN treatment plus antihypertensives compared with antihypertensives alone for hypertension in Mainland China, Japan and Thailand. Methods A Markov decision-analytic model was developed to simulate the long-term clinical events, quality-adjusted life years (QALYs) and related costs among patients who underwent RDN regimen and antihypertensive regimen in line with Netrod-HTN trial, with yearly cycles over a 30-year horizon. This study adopted the perspectives of the healthcare systems. Cost and utility inputs were collected from published literature, price databases, expert consultations, and hospital information systems. Both costs and outcomes were discounted at a rate of 5%. Model validation, univariate and probabilistic sensitivity analyses, and scenario analyses were conducted to verify the robustness of the results. Results Compared with the antihypertensive regimen alone, the RDN regimen yielded a 30.61% reduction in cardiovascular, cerebral and renal events. Cost-effectiveness analysis showed the RDN regimen yielded the most favorable incremental cost-effectiveness ratio in Japan at $3,451 per QALY, followed by Thailand at $13,932 per QALY, and Mainland China at $19,049 per QALY. Sensitivity and scenario analyses confirmed the robustness of the findings. Conclusions Netrod RDN is a cost-effective intervention from the healthcare system perspective in Mainland China, Japan, and Thailand. However, its cost-effectiveness varies across countries, reflecting differences in socioeconomic contexts. In middle- and low-income countries, appropriate pricing strategies may play a key role in enhancing its affordability and cost-effectiveness.